Sea Surface Temperature Distribution Mapping and the Relation with Coral Reef Distribution Using Modis Aqua Imagery in the Waters of Padang City - Noprianda, Renza; Mubarak, Mubarak; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2024)
Mapping sea surface temperature and coral reef distribution is vital for understanding the marine environment's dynamics and developing effective conservation strategies. The ideal temperature for coral reefs is between 27-29ºC. This research aims to describe and analyze the relationship between sea surface temperature and chlorophyll-α to the potential zone of coral reefs in Padang City, West Sumatra. The data used in this research is MODIS Aqua level 3 imagery data with 4 km resolution. The imagery processing stages include imagery data processing using SeaDAS software, namely the cropping and reprojection process, and ArcGIS software, namely the interpolation and classification process and map layouting. The results showed that the classification of the distribution of sea surface temperature in Padang City ranged from 26-29ºC, and the average concentration of chlorophyll-α distribution was 1.41 mg/m3. Based on these results, it can be concluded that Padang city waters have an ideal sea surface temperature for coral reefs and are supported by a reasonably high chlorophyll-α concentration.